2020
DOI: 10.1002/1873-3468.13788
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte‐specific protein 1 (LSP1) regulates bone marrow stromal cell antigen 2 (BST‐2)‐mediated intracellular trafficking of HIV‐1 in dendritic cells

Abstract: Human immunodeficiency virus type 1 (HIV‐1) subverts intracellular trafficking pathways to avoid its degradation and elimination, thereby enhancing its survival and spread. The molecular mechanisms involved in intracellular transport of HIV‐1 are not yet fully defined. We demonstrate that the actin‐binding protein lymphocyte‐specific protein 1 (LSP1) interacts with the interferon‐inducible protein bone marrow stromal antigen 2 (BST‐2) in dendritic cells (DCs) to facilitate both endocytosis of surface‐bound HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Interestingly, a study reported found that cases with RA achieved declining LSP1 expressing state within peripheral T cell with improved migratory ability, thereby demonstrating that defects within LSP1 signaling lead to the decline of T-cell activation threshold (46). Kulkarni et al reported that LSP1 underwent the interacting process with the interferon-inducible protein inside dendritic cell for facilitating surface-bound HIV-1 endocytosis and early endosome forming processes (47). Granulysin refers to one protein in the granules of natural killer cell and human cytotoxic T lymphocyte, exhibiting cytolysis activity against tumor and microbe (32), whereas there is no information concerning the mechanisms involved in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study reported found that cases with RA achieved declining LSP1 expressing state within peripheral T cell with improved migratory ability, thereby demonstrating that defects within LSP1 signaling lead to the decline of T-cell activation threshold (46). Kulkarni et al reported that LSP1 underwent the interacting process with the interferon-inducible protein inside dendritic cell for facilitating surface-bound HIV-1 endocytosis and early endosome forming processes (47). Granulysin refers to one protein in the granules of natural killer cell and human cytotoxic T lymphocyte, exhibiting cytolysis activity against tumor and microbe (32), whereas there is no information concerning the mechanisms involved in RA.…”
Section: Discussionmentioning
confidence: 99%
“…These virions either are endocytosed and transported for degradation or enhance cell-to-cell spread of infection. The trapped virions-BST2 complex is proposed to be endocytosed via interaction with actin-binding protein lymphocyte-specific protein 1 (LSP1) ( Kulkarni et al., 2020 ). Based on structural analysis and reasonable assumption, the LSP1/BST2 interaction would be dependent on the LSP1 N-terminal domain and YxY motif of BST2, known to interact with the actin cytoskeleton ( Mahauad-Fernandez and Okeoma, 2016 ; Kulkarni et al., 2020 ).…”
Section: Classical Function Of Bst2: Trapping Hiv-1mentioning
confidence: 99%
“…The trapped virions-BST2 complex is proposed to be endocytosed via interaction with actin-binding protein lymphocyte-specific protein 1 (LSP1) ( Kulkarni et al., 2020 ). Based on structural analysis and reasonable assumption, the LSP1/BST2 interaction would be dependent on the LSP1 N-terminal domain and YxY motif of BST2, known to interact with the actin cytoskeleton ( Mahauad-Fernandez and Okeoma, 2016 ; Kulkarni et al., 2020 ). After internalization, most of the HIV-1 is degraded in lysosomes, with the remaining minority retained in endocytic compartments and depleted through the proteasome pathway ( Smith et al., 2007 ).…”
Section: Classical Function Of Bst2: Trapping Hiv-1mentioning
confidence: 99%
“…BST-2, in addition to its functions at the cell membrane, is also known to anchor HIV-1 into the endosomal membrane and regulate intracellular trafficking of virus containing vesicles towards phagolysosomal complexes [45]. We thus investigated the interaction of BST-2 with components of intracellular trafficking and ESCRT machinery in HIV-1 infected cells.…”
Section: Cocaine Alters Bst-2 Interaction With Endosome Biogenesis Es...mentioning
confidence: 99%